Habitat Features and Their Influence on the Restoration Potential of Marine Habitats in Europe - Bekkby, Trine; Papadopoulou, Nadia; Fiorentino, Dario; McOwen, Chris J.; Rinde, Eli; Boström, Christoffer; Carreiro-Silva, Marina; Linares, Cristina; Andersen, Guri Sogn; Bengil, Elizabeth Grace Tunka; Bilan, Meri; Cebrian, Emma; et al. (Frontiers in Marine Science, 2020)
To understand the restoration potential of degraded habitats, it is important to know the key processes and habitat features that allow for recovery after disturbance. As part of the EU (Horizon 2020) funded MERCES project, a group of European experts compiled and assessed current knowledge, from both past and ongoing restoration efforts, within the Mediterranean Sea, the Baltic Sea, and the North-East Atlantic Ocean. The aim was to provide an expert judgement of how different habitat features could impact restoration success and enhance the recovery of marine habitats. A set of biological and ecological features (i.e. life-history traits, population connectivity, spatial distribution, structural complexity and the potential for regime shifts) were identified and scored according to their contribution to the successful accomplishment of habitat restoration for five habitats: seagrass meadows, kelp forests, Cystoseira macroalgal beds, coralligenous assemblages and cold-water coral habitats. The expert group concluded that most of the kelp forests features facilitate successful restoration, while the features for the coralligenous assemblages and the cold-water coral habitat did not promote successful restoration. For the other habitats the conclusions were much more variable. The lack of knowledge on the relationship between acting pressures and resulting changes in the ecological state of habitats is a major challenge for implementing restoration actions. This paper provides an overview of essential features that can affect restoration success in marine habitats of key importance for valuable ecosystem services